Screening Veterans for Syphilis: Implementation of the Reverse Sequence Algorithm - Clement, Meredith E; Hammouda, Amr; Park, Lawrence P; Maxwell, Jason; Samoff, Erika; Seña, Arlene C; Joyce, Maria (Clinical infectious diseases, 2017)
We evaluated the syphilis reverse sequence algorithm (RSA) in a Veteran Affairs facility, finding 5.5% reactive Treponema pallidum enzyme immunoassay (EIA) tests. In a subset of EIA+/VDRL-/TP-PA+ cases, 48% were previously treated. Of veterans with unknown/no prior therapy, only 45% had documentation of subsequent treatment, suggesting suboptimal interpretation of RSA results.